Dietary Supplementation of Tannins: Effect on Growth Performance, Serum Antioxidant Capacity, and Immunoglobins of Weaned Piglets-A Systematic Review with Meta-Analysis - Emmanuel Nuamah; Junior Isaac Celestin Poaty Ditengou; Fabrice Hirwa; Inhyeok Cheon; Byungho Chae; Nag-Jin Choi (MDPI AG, 2024)
In recent years, the swine industry has witnessed the withdrawal of antibiotics and continuous regulation of zinc and copper oxides in the early-life nutrition of piglets. Due to this development, alternative additives from plant sources have been extensively explored. Therefore, this study's objective was to evaluate the effect of dietary supplementation with tannins on weaned piglets' growth performance, serum antioxidant capacity, and serum immune status using a systematic review and meta-analysis approach. A total of 16 studies with parameters of interest were deemed eligible after a two-step screening process following a comprehensive literature search in the scientific databases of Web of Science, Scopus, ScienceDirect, PubMed, and Google Scholar. The inclusion criteria were mainly (1) studies involving basal diet supplemented with tannins and (2) studies with the quantification of tannin doses, while the exclusion criteria were (1) studies with pre- and post-weaning pigs and (2) challenged studies. Applying the random-effects models, Hedges' g effect size of supplementation with tannins was calculated using R software to determine the standardized mean difference (SMD) at a 95% confidence interval. Sub-group analysis and meta-regression further explored heterogeneity (PSMD < 0.05, I2 > 50%, n ≥ 10). Supplementation with tannins reduced the feed conversion ratio (p < 0.01) but increased the final body weight (p < 0.01) of weaned piglets. Chestnut and grape seed proanthocyanidin tannin sources yielded higher effects on growth performance. In addition, meta-regression models indicated that tannin dosage and supplementation duration were directly associated with tannins' effectiveness on productive performance. In the serum, the concentration of glutathione peroxidase, superoxide dismutase, and total antioxidant capacity were elevated (p < 0.01) in response to tannin supplementation, whereas malondialdehydes was reduced (p < 0.01). Likewise, increased immunoglobin M and G levels (p < 0.01) were detected. In conclusion, dietary supplementation with tannins, particularly with chestnut and grape seed proanthocyanidins, increases the productivity of weaned piglets. At the same time, it is a possible nutritional strategy to mitigate oxidative stress and stimulate gut health. Thus, supplementing chestnut and grape seed proanthocyanidin tannins in the early phase of swine production could be used to alleviate the incidence of diarrhea.